Dampak Investasi Energi Terbarukan Terhadap Pertumbuhan Ekonomi Dan Inovasi Industri: Perspektif Global Dan Implikasinya Terhadap Kebijakan Pembangunan Berkelanjutan - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aims to analyze the impact of renewable energy investment on economic growth, industrial innovation, and the implications of sustainable development policies. In the face of climate change challenges and dependence on fossil fuels, the renewable energy sector has emerged as a solution to foster greener and more sustainable economic growth. Using a quantitative approach and regression analysis, the study finds that investment in renewable energy significantly contributes to economic growth, particularly through the creation of new jobs and the reduction of energy costs. Furthermore, this investment also drives innovation in industrial sectors, such as the development of more efficient solar panels and cost-effective wind turbines. On the policy side, the study highlights the importance of fiscal incentives and government policies in supporting the renewable energy sector. Countries that implement policies supporting renewable energy show more inclusive and sustainable economic growth. These findings provide valuable insights for countries seeking to integrate renewable energy into their development policies to achieve long-term economic and environmental sustainability goals